Tingkat Kecemasan dengan Kadar Gula Darah Penderita Diabetes Mellitus Tipe II di Puskesmas Kerabitan I - Agung Ratnata; I Dewa Gede Marta Adi Kusuma; Ni Made Sintha Pratiwi (Jurnal Ilmu dan Teknologi Kesehatan Terpadu)
The primary issue in type II diabetes mellitus is the body's inadequate reaction to insulin (insulin resistance), resulting in the inability of glucose to enter the cells. Preserving mental well-being, particularly by preventing anxiety, is a method that can be employed to address insulin resistance in individuals with diabetes. The objective of this study was to establish the correlation between anxiety levels and blood glucose levels in individuals diagnosed with Type II diabetes mellitus. The research employed a quantitative correlation methodology with a cross-sectional approach. The study consisted of a sample size of 40 respondents, and the sampling method employed was non-probability sampling using purposive sampling. The findings indicated that a significant proportion of participants, specifically 33 individuals (82.5%), reported experiencing mild anxiety and had elevated blood glucose levels. The Spearman's Rho correlation test yielded a statistically significant result (p-value = 0.017, <0.05). A correlation was observed between the anxiety levels and blood sugar levels of patients diagnosed with type II diabetes mellitus at UPTD Puskesmas Kerambitan I in 2021. It is important for individuals with diabetes to prioritize their psychological well-being, particularly by avoiding anxiety as it can negatively impact blood glucose levels.